Неолиберализмот и методот на „Двојна историзација“ во Правилата на уметноста на Пјер Бурдје - Ведра (Филолошки факултет „Блаже Конески“, 2022)
In this paper, our aim is to show that there is an essential connection between Rules of Art, Pierre Bourdieu’s main work on literature, and his critique of neolib-eralism present in his later works. Namely, starting from the Postscript at the end of Rules of Art, we will show that the autonomy of the literary field obtained in the XIX century (with all its implications: the charismatic “celebration” of the author, the fetishization of literary works, the establishment of the anti-economic logic of literature and symbolic capital, the establishment of an “aesthetic gaze”, etc.) does not guarantee that the field will remain forever autonomous. In the first part, we will present and analyze the critique of the politics and economy of neoliberalism in the works of Pierre Bourdieu, with a particular emphasis on its consequences on the au-tonomy of literature and the other cultural fields. We will argue (following Bourdieu) that the only way to understand the autonomy of the literary field and the autonomy of literature in general today, is to place them in this context of neoliberal politics and economics. In the second and main part, we will present Pierre Bourdieu’s no-tion of “double historicization”, as a method through which he tries to respond to the challenges that neoliberalism poses to culture and literature. We will analyze this concept in detail, which Bourdieu sets up as an alternative to both “internal” and “external readings”. In both cases – both in the first and in the second part – we will emphasize his theoretical similarities with certain currents of Anglo-American Marxism (Raymond Williams, Terry Eagleton, Frederic Jamieson) and some other theorists, such as Theodor Adorno, Walter Benjamin and Jacques Rancière. Finally, we will try to summarize the objectives of Rules of Art through three points in this wider context.
Keywords: Pierre Bourdieu, sociology of literature, neoliberalism, autonomy, liter-ary field